2004
DOI: 10.1177/1075547004267024
|View full text |Cite
|
Sign up to set email alerts
|

The Flow of Scientific Knowledge from Lab to the Lay Public

Abstract: Abstract:This article reports on a study of how scientific knowledge about genetically modified (GM) food flows to the American public, focusing on language and message genres in the scientific literature, newspapers, and popular magazines. A comprehensive search of these literatures from 1992 to 2002 revealed a publishing pattern of scientific communication that contrasted with that found in the lay press. Examination of this difference led researchers to a scientific study on the effect of GM corn pollen on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 25 publications
2
65
1
1
Order By: Relevance
“…More people claimed knowledge of monarchs than viceroys, interesting as the state butterfly of Kentucky is, in fact, a viceroy and featured on select state license plates [64]. This interest in monarchs compared to viceroys is unsurprising given recent media coverage of monarchs in relation to other topics such as agriculture biotechnology, climate change, and gardening [65][66][67][68]. Stated prior knowledge of monarchs was correlated with both being able to identify monarchs and in willingness to conserve butterflies (concern for wildlife), which corroborates what prior studies have found [29,69,70] and lends urgency to education efforts to gain public buy-in for milkweed plantings [49,51,66].…”
Section: Discussionmentioning
confidence: 99%
“…More people claimed knowledge of monarchs than viceroys, interesting as the state butterfly of Kentucky is, in fact, a viceroy and featured on select state license plates [64]. This interest in monarchs compared to viceroys is unsurprising given recent media coverage of monarchs in relation to other topics such as agriculture biotechnology, climate change, and gardening [65][66][67][68]. Stated prior knowledge of monarchs was correlated with both being able to identify monarchs and in willingness to conserve butterflies (concern for wildlife), which corroborates what prior studies have found [29,69,70] and lends urgency to education efforts to gain public buy-in for milkweed plantings [49,51,66].…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, como nos EUA (McINERNEY, BIRD, NUCCI, 2004) Tais evoluções no âmbito da rotulagems podem ser mais bem apreciadas no contexto de um movimento globalizado na direção do chamado "consumismo político" pelo qual mudanças na produção e consumo são instituídas por meio de opções e escolhas realizadas pelos produtores e consumidores, visando melhorias ambientais e sociais (CANCLINI, 1999;SPAARGAREN, 2005 …”
Section: ______ _ Artigounclassified
“…First, press releases are a critical source of information for science journalists, but they are usually incomplete (McInerney et al 2004). Press releases from medical journals often omit key information, such as research funding, which makes the journalists' tasks more difficult (Woloshin & Schwartz 2002).…”
Section: Introductionmentioning
confidence: 99%